The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.jcot.2020.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Charcot foot reconstruction outcomes: A systematic review

Abstract: Background: Charcot neuroarthropathy is a complex condition characterised by progressive deformity, limited treatment options and a high amputation rate. Surgical reconstruction of Charcot foot has been proposed as a method to preserve the foot. However, limited information exists on the different methods of reconstruction available, their outcomes and complications. Methods: We systematically analysed published data from Jan 1993 to Dec 2018 to assess methods of fixation and associated outcomes for the surgic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 76 publications
0
23
0
1
Order By: Relevance
“…A recently published systematic review reported a fusion rate of 81% with the internal fixation technique. 32 One recent study has reported a hardware failure rate of 24% with internal fixation at a mean follow up of 31.8 months, but the functional outcomes in this cohort were satisfactory. 33…”
Section: Non-infected Charcot Deformity Correctionmentioning
confidence: 60%
“…A recently published systematic review reported a fusion rate of 81% with the internal fixation technique. 32 One recent study has reported a hardware failure rate of 24% with internal fixation at a mean follow up of 31.8 months, but the functional outcomes in this cohort were satisfactory. 33…”
Section: Non-infected Charcot Deformity Correctionmentioning
confidence: 60%
“…Published literature revealed similar outcomes with internal and external fixations options for such procedures and confirmed the vast majority of patients achieved ambulatory status following reconstruction. 3 In comparison to the other forms of internal fixation, an intramedullary (IM) hindfoot nail is considered to provide better stability and offer superior resistance to the multiplanar forces across the ankle joint exerted by the long leaver arm of the foot. An IM nail also acts as a load sharing device and thereby can potentially allow earlier return to weight-bearing.…”
Section: Introductionmentioning
confidence: 99%
“…Charcot neuroarthropathy is a debilitating illness. Charcot foot and ankle deformity can have a significant damaging effect on anyone's lifestyle, increased morbidity, and early decreased of quality of life [5] , [10] . The early recognition of a diabetic, or Charcot arthropathy is essential for a satisfactory outcome following treatment [3] , [14] .…”
Section: Clinical Discussionmentioning
confidence: 99%